PENGARUH FREE CASH FLOW, PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUB SEKTOR CONSUMER GOODS INDUSTRY DI INDONESIA PERIODE 2015-2018 - Dimas Trinanda Susanto; Erric Wijaya (Ibs Press, 2023)
Dividend policy is a result of the decision of the amount of profits earned by companies can be divided into dividends or can be replanted (profits received) as investment financing. This study aims to describe the influence of Free Cash Flow (FCF), Return on Investment (ROI), Current Ratio (CR), and Debt to Equity Ratio (DER) in the selection of shares for investment. The method used in this study is linear regression by supporting the independent factors on the dependent variable. The method in selecting samples uses a purposive sampling method and produces 26 companies. The population of this study is the companies in the Consumer Goods Industry sub-sector in the Indonesia Stock Exchange (IDX) for the period January 2015 - December 2018. Free Cash Flow (FCF), Current Ratio (CR), and Debt to Equity Ratio (DER) have a significant effect. While Return on Investment (ROI) does not affect the Dividend Payout Ratio (DPR). Simultaneously, Free Cash Flow (FCF), Current Ratio (CR), Return on Investment (ROI), and Debt to Equity Ratio (DER) related to Dividend Payout Ratio (DPR).